Sweat rate and sweat electrolyte composition in international female soccer players during game specific training - Kilding, A. E.; Tunstall, H.; Wraith, E.; Good, M.; Gammon, C.; Smith, C. (International Journal of Sports Medicine, 2009)
The purpose of this study was to determine the sweat rate and sweat electrolyte composition in female international level soccer players. Thirteen soccer players performed two 90 min soccer-specific training sessions (T1 and T2) on separate days. Hydration status was determined prior to each session and sweat loss, sweat rate and sweat composition (Na+, K+, Mg++ and Ca+) were determined from patches worn during training. The mean sweat rate during T1 and T2 was 0.50±0.20 and 0.43±0.18 L.h-1 respectively (P>0.05). The mean sweat electrolyte composition during T1 and T2 was: [Na+]: 43.9±15.0 and 46.2±7.9 mmol.L-1; [K+]: 6.1±1.1 and 5.2±1.1 mmol.L-1; [Mg++]: 0.1±0.0 and 0.1±0.0 mmol.L-1; [Ca+]: 1.2±0.5 and 0.7±0.1 mmol.L-1, respectively. When data from T1 and T2 were combined, there were no relationships between sweat rate and sweat concentration of any electrolyte. In conclusion, the sweat rate and sweat electrolyte losses in this cohort of international female soccer players, during soccer-specific training in cool conditions, were small. Electrolyte losses of this magnitude are unlikely to require special consideration in terms of optimising player hydration.